Investigating the effect of job satisfaction on increasing the productivity of human resources in the health and treatment department of Astara city (Scientific Journal of Research Studies in Future Management, 2024)
The purpose of this research was to investigate the effect of job satisfaction on increasing the productivity of human resources in the Health and Medical Department of Astara city in 2015. The statistical population of this research is made up of all the employees of the health department of Astara city with the number of 480 people, and a sample corresponding to the statistical population of the research with the number of 214 people was selected by stratified random sampling and the research was done by correlation method. Was performed. The tool for collecting information was a questionnaire that was distributed among the respondents after estimating the validity and reliability. After collecting the questionnaires, they were calculated and analyzed using statistical coefficients appropriate to the type of variables (Spearman's correlation coefficient tests and Friedman's test). After examining the main hypothesis using Spearman's correlation coefficient test, it was found that there is a significant relationship between job satisfaction and increased productivity of human resources in the health department of Astara city. is the correlation coefficient. The results of the Friedman test also show that according to the respondents, the dimensions of job satisfaction have significant differences. Also, according to the respondents, the highest average ratings were the performance of the manager or the boss, and the nature of the job, relations between colleagues, job promotion, job security, and salary are in the next ranks.